Utilization of agricultural and industrial waste as replacement of cement in pavement quality concrete: a review - Pandey A.; Kumar B. (My University, 2025)
Over the years, supplementary cementitious materials (SCM) have been successfully utilized in concrete buildings, but they have been rarely exploited in concrete pavements. In recent years, due to the growing importance of concrete pavements, researchers have begun studying the performance of various types of SCMs from pavement perspective. The overview herein assesses the existing research associated with utilizing different kinds of silica-rich waste as SCM. For this purpose, five agricultural waste (AW) comprising rice husk ash (RHA), rice straw ash (RSA), corn cob ash (CCA), palm oil fuel ash (POFA), sugarcane bagasse ash (SBA) and three industrial by-products (IB), i.e., fly ash (FA), ground granulated blast furnace slag (GGBFS) and microsilica (MS), were selected. Their effects on various properties of concrete were exhaustively reviewed. This study also furnishes reasons for limited literature on SCMs utilization in concrete pavements. Moreover, this review accentuates the previous studies’ gaps, which require further research, such as the need for dedicated standard codes for AW utilization in concrete pavements. The guidance for future research to further enhance the properties of pavement quality concrete is also given. © 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.